Molecular-weight distribution and structural transformation in water-soluble complexes of poly(acrylic acid) and bovine serum albumin - Topuzogullari, Murat; Cimen, Nermin S.; Mustafaeva, Zeynep; Mustafaev, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Interaction of polyacrylic acid (PAA) with bovine serum albumin (BSA) at different pH values and in a wide range of mixing molar ratios, gamma = n(BSA)/n(PAA), of components was investigated by size-exclusion high performance liquid chromatography with on-line refractive index, UV, light scattering and viscometer detectors. The results revealed the formation of stable water-soluble polymer-protein complexes at pH 5.0. For the soluble complexes thus formed, the number of the bound BSA molecules with one PAA molecule was expressed by a Langmuir-type equation as a function of the amount of excess BSA existing free in the solution. At saturation, one BSA molecule is bound to about 48 acrylic acid residues. The gamma-dependencies of molecular properties and structural parameters (molecular weights, molecular-weight distribution, radius of gyration, and the Mark-Houwink equation constants) of aqueous solutions of polycomplex particles have been studied. It has been concluded from these results that the complex molecule is formed by the molecular association-dissociation processes between particles depending on protein molecules in mixtures. We assume that side-by-side association of BSA-PAA complex particles took place at T 5, dissociation of the aggregates occurred by the including certain protein molecules into composition and by the compactization of polycomplex particles. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: polyelectrolyte; protein; polycomplex; size-exclusion chromatography with quadruple detection; SIZE-EXCLUSION CHROMATOGRAPHY; PERFORMANCE LIQUID-CHROMATOGRAPHY; LIGHT-SCATTERING; ANTIGEN-SPECIFICITY; POLYACRYLIC-ACID; HYBRIDOMA CLONES; IMMUNE-RESPONSE; PROTEIN COMPLEX; SYNTHETIC POLYELECTROLYTES; AFFINITY; Polymer Science